2008
DOI: 10.2215/cjn.04010907
|View full text |Cite
|
Sign up to set email alerts
|

Urine NGAL Predicts Severity of Acute Kidney Injury After Cardiac Surgery

Abstract: Background and objectives: The authors have previously shown that urine neutrophil gelatinase-associated lipocalin (NGAL), measured by a research ELISA, is an early predictive biomarker of acute kidney injury (AKI) after cardiopulmonary bypass (CPB). In this study, whether an NGAL immunoassay developed for a standardized clinical platform (ARCHITECT analyzer, Abbott Diagnostics Division, Abbott Laboratories, Abbott Park, IL) can predict AKI after CPB was tested.Design, setting, participants, & measurements: In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
558
4
15

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 698 publications
(603 citation statements)
references
References 40 publications
26
558
4
15
Order By: Relevance
“…30,31 Several small studies have found that a range on novel kidney injury-specific biomarkers, including urinary cystatin C, a1-microglobulin, N-acetylbeta-(D)-glucosaminidase, and retinol-binding protein correlate with severe AKI requiring RRT in hospitalized patients. 29,31,32 Overall, these candidate biomarkers are very promising; however, currently they are not widely available.…”
Section: Acute Kidney Injury Predictionmentioning
confidence: 99%
“…30,31 Several small studies have found that a range on novel kidney injury-specific biomarkers, including urinary cystatin C, a1-microglobulin, N-acetylbeta-(D)-glucosaminidase, and retinol-binding protein correlate with severe AKI requiring RRT in hospitalized patients. 29,31,32 Overall, these candidate biomarkers are very promising; however, currently they are not widely available.…”
Section: Acute Kidney Injury Predictionmentioning
confidence: 99%
“…NGAL is produced and secreted into the urine in response to ischemic kidney damage and is therefore a promising early indicator of tubulointerstitial damage [4,5]. Recent clinical studies show that U-NGAL reflect acute renal damage early [6][7][8][9] but may also signal chronic renal damage [10][11][12][13]. When mild to moderate increases in U-NGAL concentrations are expected it is of essence to know whether U-NGAL should be measured as absolute values or as a ratio to urinary Creatinine (U-Cr).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the levels of HNL/NGAL were significantly increased in serum/plasma and urine after cardiac surgery and paralleled reduction in renal function (12,16,19). Several immunoassays have been developed for the measurement of HNL/NGAL.…”
mentioning
confidence: 99%